Management and Leadership in Christian Educational Institutions - Arif S. Sitompul; Kristina Juniar Saragih; Desi Kristina Maralu; Hertyna Munte; Nikita Sibarani (Jurnal Multidisiplin Sahombu, 2025)
This study aims to comprehensively examine the implementation of management and leadership in Christian educational institutions through an integrated approach combining Critical Research Review (CRR), Critical Journal Review (CJR), Mini Research (MR), and Idea Engineering (IE). The study highlights the importance of integrating managerial professionalism with spiritual leadership in responding to the challenges of modernization and secularization in education. The results of the CRR and CJR indicate that the paradigm of Christian leadership has shifted from a structural orientation toward a spiritual approach that emphasizes ethical values, love, and spiritual responsibility. Through the MR, it was found that the practice of servant leadership and faith-based governance enhances motivation, solidarity, and job satisfaction. The IE phase produced a conceptual model, the Faith-Based Governance Framework (FBGF), which consists of four main pillars: Spiritual Direction, Servant Leadership, Ethical Stewardship, and Transformational Culture. This model represents an integrative synthesis of faith and professionalism, affirming that the success of Christian educational institutions is measured not only by administrative efficiency but by the extent to which Christian values are embodied throughout all managerial and leadership processes.